How to Formulate the Operation Strategy that can be a source of Competitive Advantage to Rainmaking Company? - Rizvi, Abbas Raza (2009)
Operations strategy is the heart and soul of every organisation. It is a process that every firm employs to stay competitive in the market. However, not many are acquainted about its deep seated relationship to value creation for customers and sustainable competitive advantage for the firm. This inability to understand this relationship leads them to choose wrong strategies for the organisation that obviously hamper its growth, limits its profits and in the longer run bring detriment to its mere survival.